2-Mercaptobenzoxazoles: a class of carbonic anhydrase inhibitors with a novel binding mode to the enzyme active site. Issue 59 (23rd June 2020) - Bozdag, Murat; Supuran, Claudiu T.; Esposito, Davide; Angeli, Andrea; Carta, Fabrizio; Monti, Simona Maria; De Simone, Giuseppina; Alterio, Vincenzo
Abstract : 2-Mercaptobenzoxazole represents an interesting lead compound alternative to the classical sulfonamides for the development of selective carbonic anhydrase inhibitors. Abstract : 2-Mercaptobenzoxazole is a widely used organic scaffold in medicinal chemistry. By means of kinetic and structural studies, we demonstrate that this molecule can effectively be used to inhibit hCAs showing a peculiar binding mode. The results reported here can pave the way for the development of selective CA inhibitors.